Technical Efficiency of Hybrid Corn Farming in Bontonompo District, Gowa Regency, South Sulawesi - Hikma Suci Putri; Sri Mardiyati; Amruddin, Amruddin; Mohammad Natsir (Cita konsultindo, 2025)
This study aims to analyze the factors that influence the production and technical efficiency of hybrid corn farming in Manjapai Village, Bontonompo District, Gowa Regency. The sampling method was carried out by simple random sampling with a sample size of 65 people. The data analysis used is multiple regression with the Cobb Douglas Stochastic Frontier Production Function. The results showed that the factors that significantly influenced the production of hybrid corn farming were land area, urea fertilizer, NPK (phonska) fertilizer, and pesticides. Land area, phonska fertilizer, and pesticides had a negative correlation with the production of hybrid corn farming, so that the addition of these inputs would reduce production efficiency. Urea fertilizer was positively correlated, so the addition of urea fertilizer would increase the production of hybrid corn farming. The average technical efficiency level of hybrid corn farming was 0.83 so that there was still an opportunity to increase technical efficiency by 0.17. The technical efficiency level of corn farming had a maximum value of 0.97 and a minimum of 0.42. Most hybrid corn farmers (43%) have achieved a technical efficiency level of between 0.91-0.99, so that most hybrid corn farming businesses are very efficient.